Control Indicators for Typical Persistent Organic Pollutants in Lake Sediments - LUO Xi, XIE Xiao-jing, XU Cheng-jian, ZHANG Lu, YAN Dan, TANG Qiang (长江科学院院报)
[Objective] Focusing on the composite-polluted sediments of Ya’er Lake in the Yangtze River Basin, this study aims to address the lack of control indicators for persistent organic pollutants (POPs) in environmental dredging projects. [Methods] A systematic analysis was conducted on the distribution characteristics and ecological risks of three typical pollutants: dioxins, methylmercury, and short-chain chlorinated paraffins (SCCPs). Based on the functional zoning of the lake, differentiated control indicators were proposed. The research methodology integrated comparative analysis of domestic and international standards (including China’s GB 36600—2018, Beijing’s DB11T 811—2011, and standards from Germany and Netherlands), analysis of pollutant migration and transformation mechanisms, and ecological risk assessment models. [Results]The concentration distributions of POPs in Ya’er Lake sediments were measured (dioxins: 1-50 ng/kg, methylmercury: 2-8 342 ng/g, SCCPs: 300-2 000 ng/g). Combined with the co-distribution patterns of heavy metal pollution, the response relationship between pollutant concentrations and lake functions was established. The results showed that control indicators for dioxins should be strictly graded according to lake functions: 10 ng/kg for lakes of landscape and storage functions (aligned with China’s Class I construction land standards), 5 ng/kg for lakes used for agricultural irrigation (referencing German agricultural land standards), and 1 ng/kg for lakes used for fishery purposes (based on background values and Dutch standards). For methylmercury control, the limitations of existing total mercury standards needed to be overcome. It was proposed that when the surface sediment methylmercury concentrations exceeded 5 ng/g, fishery activities should be restricted, with dry excavation identified as the preferred dredging method to minimize secondary pollution risks. For SCCPs control, a threshold of 900 ng/g was first proposed for non-fishery lakes (derived from ecological risk thresholds), while lakes used for fishery purposes required dynamic adjustments based on surrounding agricultural land data. The research demonstrated three breakthroughs: (1) it established for the first time China’s control indicator system for POPs in lake sediments, filling technical gaps in standards like GB 36600—2018 for dredging projects. (2) It revealed a high spatial correlation (R2>0.85) between POPs and heavy metal pollution in Ya’er Lake, proving that dredging according to existing heavy metal standards could simultaneously control POPs risks, thereby significantly reducing remediation costs. (3) It proposed a “function-pollutant-process” integrated control theory, offering a new paradigm for composite pollution remediation. [Conclusion] The conclusions indicate that differentiated control indicators can balance remediation costs and ecological safety. Dioxin standards for fishery water use must be an order of magnitude stricter than current soil standards, methylmercury risk control should be decoupled from total mercury metrics, and SCCPs thresholds must account for water solubility. The study provides critical scientific basis for the revision of standards such as the Technical Specifications for Environmental Dredging of Polluted Lake Sediments, and its methodology can be extended to remediation practices for other composite-polluted lakes globally.